Voluntary DNA-based information exchange and contact services following donor conception: an analysis of service users' needs. Issue 4 (1st October 2016) - Crawshaw, Marilyn; Frith, Lucy; van den Akker, Olga; Blyth, Eric
Abstract : Medical science has enabled the creation of families through the use of donor conception but some lifelong policy and practice implications are only recently being recognized. Research and practice have shown that donor conception can, for some, carry substantial long-term consequences. In this paper we present findings from a questionnaire-based study that sought to shed light on donor-conceived adults' and gamete donors' views on service and support needs when searching for genetic relatives with the aid of DNA testing. The findings demonstrate the complexity and sensitivity of providing services in this newly emerging area of need. Such provision requires collaboration between very different disciplines and agencies (scientific and psychosocial), introduces the potential for blurring of lines of accountability and responsibility, and highlights the challenges of identifying appropriate funding streams. In addition, the findings demonstrate the opportunities and limitations afforded by the use of DNA in identifying unknown genetic relatives.